(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Among the genetic disorders causing rickets because of hypophosphatemia, X- X-linked dominant hypophosphatemic rickets (XLH) is the most common, with a prevalence of 1/20,000. The defective gene is on the X chromosome, but female carriers are affected, so it is an X-linked dominant disorder. XLH associated with short stature during childhood are mostly referred to the hospital & diagnosed as vit-D deficiency rickets & received vit D before adulthood. We presented a 2-year-old boy with the complaint of walking difficulties since his 1 year of age. The patient was assessed for sociodemographic, hematological & biochemical parameters. All imaging, Laboratory parameters and positive family history confirmed the diagnosis of XLH. We treated the patient with Di basic sodium phosphate solution and 1, 25 vit D. XLH needs a good assessment, care and follow-up through a complementary medical team. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(1):52-55